Manajemen Sarana dan Prasarana dalam Meningkatkan Fasilitas Layanan Pembelajaran di MA Miftahut Thullab Daleman Kedungdung Sampang - Siti Farida; Ika Munafatus Safira (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2026)
Madrasah facilities and infrastructure are one of the important components in determining the smoothness of an institution, especially in the ongoing learning process. Therefore, good management is needed in order to continue to improve the required facilities. This study aims to determine how the planning, organization, implementation and evaluation of facilities and infrastructure management in improving learning service facilities at MA Miftahut Thullab Daleman Kedungdung Sampang. In this case, data was obtained through interviews, observation, and documentation. The study was conducted using qualitative methods with the type of field research. The results of the study indicate that the planning process was carried out by analyzing the required facilities and holding meetings attended by the principal, the vice principals, and school staff as well as creating a temporary budget to be submitted to the foundation. Organization was carried out by appointing the vice principal of facilities and infrastructure as the person responsible for implementing facilities and infrastructure management. Implementation is carried out through procurement through manufacturing, purchasing, and recycling. Funding comes from the School Operational Assistance (BOS) fund of approximately 77,850,000 annually, school-owned businesses (shops) of 20-25 million annually, grants, and donations from alumni and the community. Use is permitted by all students who need it, based on a predetermined schedule. Maintenance is carried out by the entire school community for facilities that do not require special maintenance. Inventory is recorded by recording incoming items in an inventory book. Evaluation is carried out through observation and re-analysis, followed by the elimination of damaged facilities, and the results of this evaluation are used as material for future planning. Improvements occurred in 2021, including the procurement of a library, and in 2023, the construction of a computer lab, along with the provision of five computers and one projector. In 2024, Wi-Fi was installed and two fans were added to each classroom. In 2025, a total renovation of the building was carried out, along with the addition of classrooms and the construction of a new office for male teachers.